2021
DOI: 10.3389/fpsyg.2021.706120
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Stressors Prior to-Versus During the COVID-19 Pandemic in the United States Are Associated With Depression Among Middle-Aged Mothers

Abstract: Working parents in are struggling to balance the demands of their occupation with those of childcare and homeschooling during the COVID-19 pandemic. Moreover, studies show that women are shouldering more of the burden and reporting greater levels of psychological distress, anxiety, and depression relative to men. However, research has yet to show that increases in psychological symptoms are linked to changes in stress during the pandemic. Herein, we conduct a small-N study to explore the associations between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Major events like natural disasters and war are known to have both acute and chronic impacts on physiological stress responses, as well as perceived psychological distress and mental health (Miller et al, 2007 ; Stalder et al, 2017 ). For over a year now, the Coronavirus Disease 2019 (COVID-19) pandemic has spread across the world, killing over 5 million people, damaging economies, overburdening healthcare systems, and physically and psychologically harming individuals (Courtney et al, 2020 ; Taylor et al, 2021 ). The United States was hit particularly hard by the pandemic early on, harboring nearly 20% confirmed cases and 15% of global deaths ( https://coronavirus.jhu.edu/ ).…”
Section: Introductionmentioning
confidence: 99%
“…Major events like natural disasters and war are known to have both acute and chronic impacts on physiological stress responses, as well as perceived psychological distress and mental health (Miller et al, 2007 ; Stalder et al, 2017 ). For over a year now, the Coronavirus Disease 2019 (COVID-19) pandemic has spread across the world, killing over 5 million people, damaging economies, overburdening healthcare systems, and physically and psychologically harming individuals (Courtney et al, 2020 ; Taylor et al, 2021 ). The United States was hit particularly hard by the pandemic early on, harboring nearly 20% confirmed cases and 15% of global deaths ( https://coronavirus.jhu.edu/ ).…”
Section: Introductionmentioning
confidence: 99%
“…These restrictions were effective to mitigate the spread of the virus [ 2 , 3 ], however also affect mental health and well-being. During the pandemic, a reduced quality of life [ 4 6 ], an increase in mental health problems [ 7 10 ], as well as higher levels of stress and distress [ 7 , 11 , 12 ] were shown. Taken together, research has broadly shown the various negative consequences of the COVID-pandemic, especially concerning mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological problems in patients with confirmed or suspected COVID-19, such as depression and anxiety disorders, are highly prevalent in adults and young people worldwide, regardless of cultural background [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. These findings have been shown even in the initial stages of the COVID-19 outbreak [ 11 ], and psychological discomfort seems to be present in different stages of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were found in Italy [ 19 ] and the Republic of Ireland [ 20 ]. However, it is during the periods of quarantine that individuals reported higher levels of depression, anxiety, and stress [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%